Effect of tungsten contents on the jet penetration performance of shaped charge liner based copper-tungsten composites - Tuan, Nguyen Minh; Van Toan, Nguyen; Long, Vu Thang; Duong, Luong Van; Van Trinh, Pham; Trung, Tran Bao; Dinh Phuong, Doan (Frontiers in Materials, 2024)
Herein, we investigated the effect of W content on the jet penetration performance of W-Cu shaped charge liners by using both simulation and experimental methods. The W-Cu composite liners were prepared directly by using spark plasma sintering (SPS) technique. Microstructural observations showed that W particles were uniformly dispersed within the Cu matrix. The relative density of W-Cu composites decreased slightly from 99.2 to 98.8% with an increase in the W content. The hardness of the W-Cu composite liner increased as increasing W content and reached the highest value of 209.2 HV for the composite reinforced by 60 wt.% W. Besides, the penetration depth increased and reached the maximum value of 80 mm for the composite liner containing 50 wt.% W which is improved by about 11% compared to pure Cu liner. According to simulation and experiment results, the penetration depth of the W-Cu composite liners exhibits a nearly identical trend. W-Cu composite liner containing 50 wt.% W remains the best performance compared to other composites. However, the experimental results are lower compared to the simulation results. This could be because the simulation procedure did not completely account for the actual test conditions.